An Empirical Study to Evaluate the Measurement of Leadership Management in Superior Islamic Higher Education - Fu'adi, Athok (IAIN Ponorogo, 2023)
This study aims to analyze and evaluate the determinants of the success of leadership management in superior Islamic higher education. The research sample collection method is non-probability sampling using purposive sampling. There were 422 respondents from six Islamic higher education institutions in Indonesia. PLS-SEM analysis was used to test the structural model (8 variables and 41 constructs) and 17 hypotheses. The dimensions of the measurement model have met the evaluation of the measurement and structural model. The dominant factor measured leadership management. The job description was (IP5; λ = 89.00%), and the lowest factor was infrastructure facilities (PR4; λ = 77.30%). The ability of the structural model (R2) to explain the usefulness variable based on seven measuring variables was 79.50%. In contrast, the leadership management dimension (Q2) explains 59.40% of the phenomena predicted in the field. This research contributes to the success factor of measuring leadership management supported by the influence of worthiness, accuracy, and usefulness. The involvement of eight variables can facilitate the development and conceptualization of the leadership management model of Islamic higher education.